INOVASI PEMANFAATAN EKSTRAK BUAH PEDADA MENJADI PRODUK SERBUK GRANUL INSTAN DAN PERMEN JELLY SEBAGAI PENINGKAT DAYA TAHAN TUBUH - Lestari, Uce; Sari, Eza Permata; Siagian, Martha Veronica Helena (Universitas Jambi, 2024)
ABSTRACTPedada fruit extract contains chemicals in the form of flavonoids, polyphenols and tannins. The flavonoids contained in pedada fruit are useful as very strong antioxidants, not only that, the very high vitamin C content in pedada fruit can be used as an immune booster. Based on this, the idea emerged to create an innovative functional drink product in the form of instant granule powder from pedada fruit as an immune booster and pedada fruit jelly candy as an antidote to free radicals. The aim of this Community Service is to improve public health through promotive, preventive, curative and rehabilitative efforts for the community to avoid disease infections and open business opportunities for Nurchery MSMEs to produce instant granule powder and pedada fruit jelly candy which has the power keep it longer. The methods implemented include counseling or outreach to the community as well as assistance to MSMEs regarding the production of instant granule powder and jelly candy. The results obtained from this PPM are the use of instant granule powder and pedada fruit jelly candy by the community as a health drink to increase endurance as well as the development of Nurchery MSMEs in producing instant pedada fruit granule powder with the trademark name